To See or Not to See: Power and Visuality in Modern Art (Lalitkala Pragya ललितकला प्रज्ञा, 2026)
Our ways of seeing and the representational strategies used in modern visual art often differ, as they reflect perspectives that do not fully fit with everyday perception. This research examines how specific visual cultures or subcultures shape particular modes of visualization and representation. Visualization begins with biological vision but is shaped by culture, ideology, and, most importantly, power relations. The process of visualization starts with biological vision, gets modulated through culture, ideology and predominantly through power dynamics. All in all, it encompasses two ways of seeing: what the audiences want to see and how/what the visual artists want to represent the subject. Theoretically, the discourse analysis of visual culture inherits models of knowledge, thought, and ideation from philosophers and thinkers, predominantly Michael Foucault’s ‘will to power’, Fredrick Jameson’s ‘will to style’ and ‘will to automatism,’ or ‘automatism of the camera-eye’s view,’ and Walter Benjamin’s ‘‘the instrumentality of a non-living agent’ including other relevant theories. Some representative modern paintings by selected masters have been used as primary text of discussion. The discussion concludes that the central question in visual culture is “To see or not to see” the subjects. Beholder’s visualization (which ultimately constitutes a simulated mass psyche) and visuality of the subjects are related to power dynamics.  Modern art is all about manifestation of this power-driven visual culture. The discussion on the selected paintings infer that the focal agenda of the modernist painters is to embody the subjects from a different vector that the spectators, ruler or surveyor overlook. They tend to manifest the voice or agencies of characters who are mostly subdued.